Soziale Elite und Christentum Studien zu ordo-Angehörigen unter den frühen Christen - Weiß, Alexander (Millennium-Studien / Millennium Studies, 2015)
The notion that early Christianity was a "lower class religion" is surely outdated. Yet the extent to which members of the social elites turned to the new faith remains a matter of intense scholarly dispute. Many researchers argued against the idea that the social elites were already represented among early Christians. However, the sources give extensive evidence that senators and local officials were among the Christians of the 1st century CE.